Discover spiders (Bath: North parade publishing Ltd, 2019)
A Visual Guide to these Eight-Legged Wonders. Spiders are in the arachnid class, but not all arachnids are spiders. Most spiders use a web to catch their prey, which comes from spinneret glands on their abdomen, and each gland produces a different kind of silk - some sticky, some fine, and some for building. This Discover Spiders book provides a valuable introduction to these creatures and their world.
Juvenile
Keywords: Insects Insects$1 (BJuvenile literatures; Non fiction- Juvenile literature